Gender differences in squash performance and strategy at the elite level: A notational analysis - Carboch, J.; Dušek, P. (Journal of Physical Education and Sport, 2023)
There are various strategic and tactical situations during every point of a squash match, where either male or female players need to make quick decisions. Performance analyses can provide important data for scientists, coaches and players. However, there are few studies on squash compared to other sports games. The aim is to compare the game characteristics and rally pace in the elite level of men's and women's squash matches at Professional Squash Association (PSA) tournaments. We watched video recordings of men's and women's matches at the elite level of squash. We analysed 18425 shots in 14 men's matches and 10014 in 11 women's matches. We found a significant difference in the point duration of men's matches 25,1±3,5s compared to women's matches 17,2±3,9s (p<0,001), and the men's matches were played at a significantly faster rally pace 1,34±0,05s compared to women's matches 1,39±0,05s (p<0,05). There was no statistical significance between winners and losers for the rally pace of specific shots. Regarding shot frequency, both male and female players hit more backhand shots than forehand shots in the ratio 2to1, the drive shot was the most frequent, and the most common error was when the players hit the ball too low onto the front wall. More than 50 % of all shots hit the ower third of the front wall in both genders. These observed game indicators show differences in the game characteristics and performance between the genders at the elite squash level. This information can help coaches and players to adopt gender-specific training strategies.